Collingwood and the crisis of western civilisation : art, metaphysics and dialectic - Murphy, Richard (Richard L.) (British idealist studies. Collingwood, 2008)
This book argues that R.G. Collingwood's philosophy is best understood as a diagnosis of and response to a crisis of Western civilisation. The various and complementary aspects of the crisis of civilisation are explored and Collingwood is demonstrated to be working in the traditions of Romanticism and 'historicism'. On these subjects, the theories of Collingwood and Ortega y Gasset are contrasted with those of Nietzsche and Weber.